If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4v + -4) = 80 Reorder the terms: -4(-4 + 4v) = 80 (-4 * -4 + 4v * -4) = 80 (16 + -16v) = 80 Solving 16 + -16v = 80 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -16v = 80 + -16 Combine like terms: 16 + -16 = 0 0 + -16v = 80 + -16 -16v = 80 + -16 Combine like terms: 80 + -16 = 64 -16v = 64 Divide each side by '-16'. v = -4 Simplifying v = -4
| 4(1+4n)=68 | | 5x=2.5 | | -3(3+3r)=-45 | | n-13=23 | | 8(2-x)-x=2 | | 3v^2-5v-2= | | 3(3-4x)=45 | | 3(5+c)=2(c+6) | | 7x-(3-x)=3x+4 | | x+(3x+5)=180 | | -4g+9=-4g+9g | | XY+5x-3y-7x+2xy-4z= | | 5x-3x=13-7 | | 4(x-3)+1+2+3=0 | | 22-14=4(x-8) | | 6-9(x+2+3)=0 | | 6a+14= | | 3(3x+2)+4(x+2)=0 | | 20b^2c-17bc-63c= | | X^2-14+33=0 | | 25v^2+19v+4= | | -7a-2y+7+2y+5a= | | 4x+20=x+32 | | 5x^2-22x-15= | | 4x^4+9x^3-2x+7=0 | | (7+w)(2w-9)=0 | | 4x^2-14=0 | | 6x-36+4=8x+16-10 | | 3(x+2)+5x-(x-1)=-2x+1 | | 4a^2-7a-28a+49= | | 2m= | | 4x^4+9x^3-2x+7=1482 |